Prospecção da ação leishmanicida de inibidores de proteases extraídas de Bauhinia forficata Link - FIGUEREDO, Aline Santana (2021)
Introduction: Leishmaniasis is part of the group of neglected diseases, caused by protozoa of the genus Leishmania, being endemic in 98 countries. The therapy used for this disease is associated with high toxicity, difficult administration, high costs and parasitic resistance. Therefore, the search for new drug alternatives, more effective and less toxic is necessary and protease inhibitors are crucial molecules, since Leishmania proteases are involved in several physiological and pathological mechanisms. Aim: To identify the chemical constituents of the Bauhinia forficata Link extract, as well as the cytotoxic effect of the extract and the aspartic protease inhibitor fraction on Leishmania (L.) amazonensis. Materials and methods: firstly, the preparation of the extract was carried out, followed by the dosage of proteins, through the Bradford method, and then these proteins were identified through the electrophoresis method. Another method performed was the study of the chemical constituents present in the extract, in which the Matos phytochemical screening test was used, followed by thin layer chromatography, and the flavonoid contents were determined by high performance liquid chromatography. After chemical characterization, in vitro cytotoxicity tests were performed using sheep erythrocytes and immortalized cells of the RAW lineage, and in vivo toxicity tests in Tenebrio molitor larvae. As for the leishmanicidal activity in Leishmania amazonensis promastigotes, the assay was performed using the MTT method (3-(4,5-dimethyithiazol2-yl) -2,5- diphenyltetrazolium bromide), and the antiamastigote activity was performed with RAW cells. Results and discussion: Derivatives of quercetin and kaempferol were the main metabolites found in BF-CA. After isolation of the inhibitor of aspartic profease (BFI), 130.6 ± 29.94 μg of protein was obtained, with a yield of approximately 4.41 ± 0.77 %, that is, 4.41% of the proteins of BF-CA. The extract and BFI did not show cytotoxicity to sheep erythrocytes. In RAW cells, the extract and the inhibitor tested (BF-CA and BFI) showed a cytotoxic concentration for 50% of the cells (CC50) of 166.5 μg/mL and 371.3 μg/mL, respectively, and for pentamidine with CC50 of 15.24 μg/ml. By analyzing the inhibitory concentration in 50% (IC50) of the extracts on the promastigote forms of Leishmania amazonensis, we obtained an IC50 of 54.9 μg/mL for BF-CA and 8.33 μg/mL for BFI, which exhibited toxicity at almost all concentrations tested. When evaluating the inhibition of proteases, BFI inhibited 44.66% of the activity of commercial pepsin protease and inhibited 40% of the serine protease secreted by L. amazonensis, LSP III. Conclusion: Therefore, BF-CA has a composition rich in flavonoids, with proven leishmanicidal action in promastigote and amastigote forms, evidenced by the reduction of infection. As for BFI, it inhibited the activity of the serine protease secreted by L. amazonensis (LSPIII), making it a potential therapeutic target, as it is capable of interfering in the pathophysiology of leishmaniasis